A model of sustainable production: ecological and economic benefits of high-gloss UV-coating in offset printing without a relevant loss in gloss quality - Radermacher, Kirsten (Journal of Print and Media Technology Research, 2023)
This paper presents a guideline for enterprises to realize sustainable production in compliance to economic interests. A special perspective on the product quality that is perceptually noticeable, or required for customer satisfaction, enables to reach economic benefits not conflicting in respect with the principles of sustainability. Therefore, the model of sustainable production was exemplarily demonstrated by the glossiness of cardboard packaging. The investigation was mainly concentrated on the gloss measurement and perception aiming to define a threshold of perceptual gloss that gives information about the product quality required. Gloss has been a part of research work for decades. However, there are no researchers known who were able to quantify a threshold that inform about noticeable gloss differences. Furthermore, the measurement technology of gloss is much more complex than expected. The specular gloss is still the main important feature, and is broadly the essential measure in practical application. However, further gloss types are implemented in so-called goniophotometric instruments. In this paper, the currently available knowledge in gloss perception and measurement is used to generate a measure of perceptible gloss differences. Influencing factors affecting the environmental performance of high-gloss cardboard packages are presented, and suitable methods for measurement are employed. For high-gloss coated cardboard packaging, the volume of the coating roller and the intensity of the UV-curing unit reveal potential for sustainable production under consideration of the threshold of 2.0 Gloss Units that is recommended from a visual test performed. Considering the assumption made for the product example, 0.99 ± 0.65 g ∙ m−2 of UV-coating and 6.6 ± 3.8 kWh of energy could be saved. The integration of these scenarios in life cycle assessment (LCA) on coatings will help to assume whether these savings are crucial in the whole product life cycle. This paper gives first impressions.